2015
DOI: 10.5419/bjpg2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Microbial Sulfate Reduction by Molybdate

Abstract: Hydrogen sulfide generation in oil production is a constant cause of concern. In several cases this phenomenon occurs due to the action of sulfate-reducing bacteria. Various methods, including biocides and nitrate addition, have been used to control the activity of these microorganisms, but they are expensive and have side effects. Other inhibition methods, such as the use of molybdate, have received much less attention. This study performed a kinetic test for the inhibition of sulfate reduction, and shortterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 1 publication
1
19
0
1
Order By: Relevance
“…The starting point for the development of inhibition model associated with the results of the tests of inhibition of microbial sulfate reduction using molybdate previously presented [18] and showed that the sulfate reduction activity and generating sulfide by sulfate-reducing bacteria (SRB) are inhibited when the medium has a molar ratio molybdate/sulfate equal to 0.004. Given this, molybdate transport simulations in the bioreactor were performed for different scenarios.…”
Section: Simulation Of the Inhibiting Microbiological Reduction Of Sumentioning
confidence: 99%
See 4 more Smart Citations
“…The starting point for the development of inhibition model associated with the results of the tests of inhibition of microbial sulfate reduction using molybdate previously presented [18] and showed that the sulfate reduction activity and generating sulfide by sulfate-reducing bacteria (SRB) are inhibited when the medium has a molar ratio molybdate/sulfate equal to 0.004. Given this, molybdate transport simulations in the bioreactor were performed for different scenarios.…”
Section: Simulation Of the Inhibiting Microbiological Reduction Of Sumentioning
confidence: 99%
“…Consider first the case in which the reactor is continuously fed with a synthetic saline modified Postgate C with 960 mg/L (10 mM) of sulfate ions and all other nutrients necessary for complete reduction of the sulfate present in the medium are available [18]. According to the results obtained by de Jesus et al (2015) in this situation the inhibition of bacterial activity is achieved when throughout the bioreactor a molybdate concentration profile of 6.4 mg/ L is reached.…”
Section: Simulation Of the Inhibiting Microbiological Reduction Of Sumentioning
confidence: 99%
See 3 more Smart Citations